Diesel/biofuel exhaust particles from modern internal combustion engines: Microstructure, composition, and hygroscopicity. (1st October 2015) - Popovicheva, Olga; Engling, Guenter; Lin, Kuan-Ting; Persiantseva, Natalia; Timofeev, Mikhail; Kireeva, Elena; Völk, Peter; Hubert, Andreas; Wachtmeister, Georg
Highlights: Diesel/biofuel combustion emissions from modern internal combustion engines are analyzed. Particulate microstructure is revealed in soot and fly ash groups as well as their hygroscopicity. Most polluting conditions with respect to fouling of the exhaust system are indicated. Multicomponent composition is impacted by both fuel and operation conditions. Abstract: Changes in fuel characteristics and design of diesel engines have been applied in the last decades to reduce pollutant emissions in the transportation sector. Characteristics of exhaust particles and their environmental impacts need to be brought up to date. In this study, diesel and rapeseed oil were used in modern internal combustion engines (BMW and John Deere) in order to simulate stationary and transient non-road driving conditions, with attention on fouling processes in the exhaust system and contributions to atmospheric pollution. Engine particulate exhaust samples were subjected to individual particle analysis and bulk physico-chemical characterization with respect to polycyclic aromatics, water-soluble organic carbon and inorganic ions. Functionalities of alkanes and oxygen-containing compounds were determined in the exhaust particles. The emitted particles with similar morphology and composition were separated in specific groups, revealing the exhaust microstructure. In-depth characterization of individual particle composition provided insights into the relationship of chemical composition and hygroscopicity, based on fractionation analysis. With improved characterization of diesel/biofuel combustion emissions we demonstrate that the multicomponent composition of modern internal combustion engine exhaust is impacted by both fuel properties and operation conditions.